Pengaruh Kualitas Pelayanan, Citra Merek, Harga, dan Kualitas Produk Terhadap Loyalitas Pelanggan - Aditya Dwi Putra; Nurul Azizah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
One of the beverage products that has many fans in Indonesia is coffee. Coffee is one of Indonesia's leading plantation commodities that has an important role, especially as a source of foreign exchange, a provider of employment. Jokopi is one of the coffee shop brands that has a contemporary coffee drinking trend. With the tagline